2021
DOI: 10.1002/marc.202100284
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Hyperbranched Functional Materials via Green Polymerization of Readily Accessible Levoglucosenone‐Derived Monomers

Abstract: The homopolymerization in basic conditions of the recently reported bis( -lactone), 2H-HBO-HBO, is herein described for the first time. The solvent-free polymerization of this pentafunctional levoglucosenone (LGO) derivative affords fully renewable poly(vinyl-ether lactone) copolymers with a highly hyperbranched structure. This investigation stems from the polycondensation trials between 2H-HBO-HBO and di(methyl carbonate) isosorbide (DCI) that fails to give the anticipated polycarbonates. Such unexpected beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…), the 13 C spectrum displayed only three CO signals with intensity ratios of 1 : 2 : 1 corresponding to the endo – endo , endo – exo / exo – endo , and exo – exo carbonate groups, respectively. 54…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), the 13 C spectrum displayed only three CO signals with intensity ratios of 1 : 2 : 1 corresponding to the endo – endo , endo – exo / exo – endo , and exo – exo carbonate groups, respectively. 54…”
Section: Resultsmentioning
confidence: 99%
“…ratios of 1 : 2 : 1 corresponding to the endo-endo, endo-exo/exoendo, and exo-exo carbonate groups, respectively. 54 In an attempt to quantitatively determine the relative fractions (in %) of the repetitive units of the PC structures, the deconvolution of the 1 H NMR spectra was performed to separate the overlapping peaks and determine the corresponding area and intensity of each signal.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…149 Allais, Fadlallah et al reported on the copolymerisation between ISB, DMC and bis-γ-lactone, a monomer derived from levoglusenone, observing almost exclusive fast homopolymerisation of the bis-γ-lactone comonomer. 150 DACs/diols polycondensation represents a promising strategy for the preparation of commercially relevant renewable-based polyesters. It is likely that this technology will reach high TRLs in the next 10-15 years, therefore, the commercial relevance of this process must be combined with a detailed assessment of its economical and environmental viability, as well as with an evaluation of the toxicity, ecocompatibility and end-of-life fate of the resulting polyesters.…”
Section: Applications Of Dialkylcarbonates In Polymer Synthesismentioning
confidence: 99%
“…149 Allais, Fadlallah et al reported on the copolymerisation between ISB, DMC and bis-γ-lactone, a monomer derived from levoglusenone, observing almost exclusive fast homopolymerisation of the bis-γ-lactone co-monomer. 150…”
Section: Dialkylcarbonates In Polymer Synthesis and Biopolymers Modif...mentioning
confidence: 99%
“…DCI can be obtained in high yield by methoxycarbonylation of isosorbide in the presence of DMC, and it is one of the potential monomers for the synthesis of functional PC. 92,120 Recently, Aricò et al 121 used the levoglucosyl triol monomer citrate triol (triol-citro) to achieve polycondensation with DCI to synthesize PC containing both linear and dendritic units. The novel PC is composed entirely of bio-derived groups with citronellol side chains, leading to the cross-linking of the side chains induced by UV light irradiation.…”
Section: Bio-based Polycarbonates From Isosorbide Monomersmentioning
confidence: 99%